Crack-free Al0.5Ga0.5N epilayer grown on SiC substrate by in situ SiNx interlayer. (January 2016) - Tao, Pengcheng; Liang, Hongwei; Xia, Xiaochuan; Chen, Yuanpeng; Yang, Chao; Liu, Jianxun; Zhu, Zhifu; Liu, Yang; Shen, Rensheng; Luo, Yingmin; Zhang, Yuantao; Du, Guotong
Abstract: The crystal quality and stress state of Al0.5 Ga0.5 N epitaxial layers on 6H-SiC wafers by introducing an in-situ deposited SiN x nanomask layer grown by metal-organic chemical vapor deposition (MOCVD) were investigated. A SiN x interlayer with various growth times was inserted to the Al0.5 Ga0.5 N epilayers. The full width at half maximum (FWHM) of X-ray diffraction peaks and the density of etch pits decreased dramatically by the SiN x interlayer, indicating an improved crystalline quality. Also, it was found that the crack density and biaxial tensile stress in the Al0.5 Ga0.5 N film was significantly reduced by in situ SiN x interlayer from optical microscopy, photoluminescence spectra and Raman spectra. Finally, a crack-free 1.8 μm thick Al0.5 Ga0.5 N epilayer grown on 6H-SiC substrate using the optimized SiN x interlayer growth time was obtained.